(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In this article, the process of socialization of elementary school students and the increase of student activity and attention to the lesson during teamwork, the ways and methods of using role-playing games in mother tongue classes are discussed.